2014
DOI: 10.1051/shsconf/20141201086
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Highland Development through Stakeholders’ Perceptions on Agro EcoTourism in Cameron Highlands: A Preliminary Finding

Abstract: Abstract. Cameron Highlands was discovered in 1885 and was developed as a hill station. It first served as a quaint retreat destination for the British residence where the urban morphology of its little town centres were strongly characterised by colonial architecture such as bungalows, institutional buildings and government offices, shophouses and market stalls. Eventually due to economic pressure and location potentials, more land was opened for tea plantations and vegetable and flower industries. Conversely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…Meanwhile, the area of 10.8 % is classified as high susceptible erosion zone with total annual soil loss greater than 15 ton ha -1 yr -1 . This finding was also found consistent with the studies conducted in the same catchments area [5,[36][37][38][39]. Reference [38] reported that the risk of soil erosion in Cameron Highlands is generally law, however, the erosion rate is on increase with a greater tendency of potential soil loss.…”
Section: E Susceptibility Of Erosion and Risk Zoningsupporting
confidence: 90%
“…Meanwhile, the area of 10.8 % is classified as high susceptible erosion zone with total annual soil loss greater than 15 ton ha -1 yr -1 . This finding was also found consistent with the studies conducted in the same catchments area [5,[36][37][38][39]. Reference [38] reported that the risk of soil erosion in Cameron Highlands is generally law, however, the erosion rate is on increase with a greater tendency of potential soil loss.…”
Section: E Susceptibility Of Erosion and Risk Zoningsupporting
confidence: 90%
“…New highways constructed in 2003, provide a better land access for agriculture products transportation and reduce the cost and time to deliver the goods (Barrow et al 2009). The 7th Malaysia Plan (1996-2000 has encouraged the participation from local communities to ensure the success of agro-tourism (Mohd Ariffin et al 2014;Mansor et al 2015) and strategies have been created to expand the agriculture potential and other relatable sectors specifically agro-tourism in the 8th and 9th Malaysia Plan (2006. According to RTD 2018a, the tourism focused on agro-tourism, eco-tourism, cultural and heritage tourism.…”
Section: Rozimah and Khairulmaini 2016mentioning
confidence: 99%
“…Relationship between land use change, agriculture practices, and agro-tourism with highland river water quality Approximately, 66% of the land in Cameron Highlands have gradients more than 20°that can trigger the soil erosion and landslides (Aminuddin et al 2001;Gasim et al 2010;Khairulmaini and Fauza 2010;Kunasekaran et al 2011;Tan and Mokhtar 2011;Mohd Ariffin et al 2014;Rendana et al 2015;Rozimah and Khairulmaini 2016). Sandy soil and high-average annual rainfall increase the movement of soil (Aminuddin et al 2001).…”
Section: Plastic Rain Shelter Fertigation Hydroponicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrotourism, which has existed in Europe, North America, and other parts of the "global North" for many years (Busby and Rendle 2000), has more recently gained growing attention in developing countries, including Thailand (Brscic 2006; Na Songkhla and Somboonsuke 2013; Choo and Petrick 2014; Rogerson and Rogerson 2014;Shaffril et al 2015). Although it would seem to be a useful strategy to develop mountain agriculture and improve farmers' income and quality of life, there has been relatively little research directed at mountain agrotourism in developing countries, including in Southeast Asia (Ariffin 2014).…”
Section: Does Agrotourism Benefit Mountain Farmers? a Case Study In Pmentioning
confidence: 99%